Event Related Outdating A Fairy Tale Comes True - Chadwick, Sandy (Operating Room Nurses Association of Canada Journal, 1994)
Legend tells us that once upon a time, in a hospital basement far, far, away, an 0.R. nurse found a package wrapped in newspaper and tied with a string beneath a pile of obsolete total hip instruments. The package bore an inscription which read, “Sterile bandages” and was dated twenty years previously. The 0.R. nurse grabbed the package eagerly and took it to the Chief Wizard of theLab, who submitted the mysterious package to all manner of tests. Lo and behold, the package was declared to be sterile! There was much rejoicing throughout the 0.R. kingdom. There was amazement that past hospital dwellers were able to create and maintain sterility under such conditions, for this was contrary to all that the OR and CSR kingdoms held to be true. There was rejoicing, and there was wonder, but unfortunately little else, for both the OR and the CSR continued to outdate based on time related criteria. And so it has remained in most ORs and CSRs to this very day. This is where the fairy tale ends and event related outdating begins.